Sistem Pengukuran Kualitas Website Penelitian dan Pengabdian Masyarakat I-Gracias Menggunakan Metode Webqual - Asha Gita Dinia; Citra Wiguna; Auliya Burhanudin (Maranatha University Press, 2022)
As a learning center based on Information and Communication of Technology (ICT), the Telkom Purwokerto Institute of Technology has an I-Gracias website, one of which has a PPM menu, the menu functions to enter research data, scientific publications and lecturers' internal community service so that they can be managed by the public. LPPM. Based on the survey that has been carried out, it is known that there are several problems with the I-Gracias PPM system, such as an unattractive and quite confusing system display, menus that do not work properly, processes that are still not efficient, functions that are needed and do not exist in the system, and the lack of socialization of the use of the system to lecturers with the main problem that there is no prioritization of the quality of system performance which includes aspects of usability, quality of information and quality of interaction. The results of the questionnaire show that 95% of respondents agree with the quality measurement of the I-Gracias PPM system. Website-based PPM systems need to be measured using a web testing method, namely the Website Quality method or what is called WebQual as a determinant of criteria for measuring system quality in this study. This study resulted in the value of measuring the quality of the system in accordance with the user's perception so that the organizers can find out and correct the deficiencies that exist in the system. Quality measurement is carried out using a website-based information system.